Choose-ables, Sensing and Sense-making: A study of Orders of Choice - Dodd, Lorraine (Cranfield University, 2020)
There has long been academic study into decision-making to look at different strategies that are used to select a course of action from a set of decision options. The subjects making these decisions, the decision-agents, tend to be objectively rational with selections made based on maximising expected utility or minimising probability of loss. There is, however, a lack of research into how the options for choice are settled upon in the first place. It is this topic of choice-making that is the focus for this research study, which covers the subjective nature of choices being ‘imagined deemed possible’ in the form of ‘choose-ables’ as related to what that subject might be sensing and understanding. Chooseables are a subject’s options for choice, given the nature of their sense of context and their felt conditions. In this respect, choose-ables are subjective and relative respectively. The main proposition is that any subject has an associated range and scope of choose-ables, and that these can be organised according to the nature of the choose-ables open to that subject. The research gap being addressed by this PhD study exists due to the lack of a formal theoretical framework to examine why and how a subject’s options for choice are settled upon by that subject. Therefore, the contribution made by this PhD by Published Works is an order of choice framework that has a two-fold application: first, the explanation of what might shape the nature and scope of a subject’s choose-ables; second, a way of formally appreciating and analysing the implications of those choose-ables for a subject’s sensing and sense-making; hence, potentially for ‘modelling’ the forming of their subjective potential for choice-making and any emergent behaviours. This thesis presents a seven-fold framework for orders of choice, applicable to a range of subjects; from agent-based algorithms and cells through to people, organisations and political institutions. A key assumption is that each subject makes choices according to a principle of discomfort avoidance. Subjective preferences, interests and needs relate to a subject’s scoping of their choose-ables, according to a subject’s sensing and sense-making of their circumstances. Preservation of a subject’s sense of comfort acts as a central concept of subjective ‘settling’, which governs the nature of the choose-ables according to where any subject is in relation to their context. The overarching research question is: From where might a subject’s choose-ables emerge; and how might these choose-ables moderate, or be moderated by, that subject’s sense-making and their focus of attention? The portfolio of seven published works covers the supporting theories and also describes the background experimental work that prompted the development of the linking of the two underlying theories: Catastrophe Theory and Cultural Theory. This thesis formalises the links between these two theories and Shackle’s (1976) work on choose-ables. The orders of choice are aligned and associated with other levels of capability, organisation, and adaptation; then developed into a nested framework based on Catastrophe models with further understanding drawn from other, related, theories about levels of capability and organisation, drawing on relational frameworks in Cultural Theory. The framework contributes to knowledge by providing a formal mathematical basis for a descriptive language that can be applied in order to understand and appreciate where any subject might be in terms of their choose-ables, their sensing and their sense-making, and to help to explain why. A significant conclusion is the centrality of a subject’s concept of value for their choice-making.
PhD by Published Works